(untitled) (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Change of voice is one of the common complaints in ENT practice and hoarseness of voice is the commonest symptom of changed voice quality. Hoarseness is invariably the earliest manifestation of conditions directly or indirectly affecting the voice apparatus. Though most common causes of hoarseness are benign and vocal abuse is the commonest among them, but we should always investigate for more sinister pathology like malignancy. The aim of this study was to compare the diagnostic yields of fibreoptic laryngoscopy (FOL) with that of indirect laryngoscopy in the diagnosis of vocal cord lesions. Objectives: To compare fibreoptic laryngoscopy (FOL) and indirect laryngoscopy in the diagnosis of vocal cord lesions as the cause of voice change. Methods: This is a cross-sectional study which has been conducted in the Department of ENT and Head Neck Surgery, SSMC Mitford Hospital with a sample size of 87 cases for a period of six months from 10th February’ 2020 to 9th August’ 2020. The patients with vocal cord lesions were selected according to the eligibility criteria by purposive sampling. Results : On indirect laryngoscopic examinations, 29.89% were vocal cord polyp, 16.09% suspected vocal cord neoplasm, 14.94% vocal cord edema, 11.49% vocal cord nodule, 5.74% vocal cord palsy and 2.61 were ulcerative lesion of vocal cords whereas poor view were in 18.39% cases. On fibreoptic laryngoscopy (FOL), 29.89% were vocal cord polyp, 19.54% suspected vocal cord neoplasm, 17.24% vocal cord edema, 16.09% vocal cord nodule, 8.04% vocal cord palsy and 6.90% were ulcerative lesion of vocal cord. 2.30% revealed normal study. Study showed that fibreoptic laryngoscopic examination is superior to indirect laryngoscopy in diagnosing vocal cord lesions. Conclusion : Fibreoptic laryngoscopy (FOL) is significantly superior to indirect laryngoscopy in the diagnosis of vocal cord lesions. Indirect laryngoscopy sometimes may miss to diagnose a sinister disease like malignancy. Bangladesh J Otorhinolaryngol 2023; 29(1): 24-31